(untitled) (Medical Forum Monthly, 2024)
Objective: This study explored how second year medical students of Poonch Medical College related studying in medical college with their social activities. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted with the first batch of students at PMC in Rawlakot AJ&K from January 2013 to July 2014. Materials and Methods: This study obtained data in a purposive sample from the entire second year class using a structured self-administered questionnaire, with 88% response rate. Results: Of total 88 respondents, 63 girls (72%) and 25 boys (28%) with a mean age of 19 participated. More than 80% respondents had many friends, 81% girls and 36% boys didn’t have time to meet them ((p<.000). Around 89% girls and 68% boys didn’t have time to play ((p.029), 49% girls and 44% couldn’t see their families (p<.197), 40% hostelite and non-hostelite could play (p<.991), and 76% boys and 65% girls perceived burdensome medical study which deprived them from regularly meeting with their family and friends. Conclusion: Findings of this study have broader implications for furnishing academic environment in medical institutions of Pakistan more conducive, supportive and effective. Medical institutionsshould review their curriculum and teaching/learning schedules and try to redesign their educational programs keeping a balance between study load and the social life of a medical student. Students should also be encouraged to set their educational and social priorities and try to ensure this balance.